The relationships among the perceived importance of ASNB's agent functions, selected demographic and customer satisfaction on services rendered by ASNB's agent: Maybank, Taman Melawati, Kuala Lumpur / Ezdiana Hanani Hj Tumingan - Tumingan, Ezdiana Hanani (Faculty of Business and Management, 2005)
The service rendered by ASNB's agent is the focus of the study. Understanding the customer satisfaction towards the function performed by ASNB;s agent and the services provided by ASNB;s agent is a critical issues for principal, agent and unit holders. The major findings of this research found that for the function performed by ASNB's agent, the unit holders perceived it as important function to them and ranking 1st is an ability of the agent to provide a standardized service for the unit holders. Besides that, the level of customer satisfaction results to satisfactory for all services provided by ASNB's agent. From this research, it indicates that there is a significant relationship between perceived importance of function performed by ASNB's agent and customer satisfaction. It also indicates that there is a significant relationship between selected demographic and customer satisfaction on services provided by ASNB's agent.